Traditional Healing Practices Using Herbal Dosage Forms and Other Agents by Magar Community of Gulmi District, Nepal - Khanal, D P; Raut, Bechan; Magar, Yamuna T (Journal of Manmohan Memorial Institute of Health Sciences, 2020)
Correction: The page numbers were changed from 24-41 to 20-38 on 31/08/2020.Background: The distinctive climatic and ecological conditions make Gulmi a unique existence for a large Biodiversity. For thousands of years, Magars are living in this area and they are mostly dependent on agriculture. They follow their own ancient traditional healing practices. But socio-cultural activities of the Magars community are directly and indirectly related to the plants resources. Therefore, this study mainly focuses on the survey of traditional healing practice including plant used and dhami-jhakri of Magars community of Gulmi district Nepal.Objective: The main objective of the study was to explore the traditional healing practices and identify the plants used by Magar Community of Gulmi District, Nepal for their healing practices.Methodology: It was descriptive cross sectional study. A survey was performed using open ended questionnaires and face to face interview with the healers of Magar community of Gulmi, district Nepal.Result: Various belief of causes of diseases on traditional healers were found. They were vayu-batas,masan, bhut-pret, Grahadasha, Boksi, Pitri risako, kul deuta risako etc . Moreover the diseases were diagnosed by Observation of eye, Observation of nadi, Phukphak, Jantarmantar, Bali, Puja, Akcheta herne etc.Spiritual based four healing techniques and/or approaches, Phukphak, Bali, Jantar-mantar and kul bigreko, used by traditional healers. Healers were using 31 plant species belonged to 23 families for preparing different poly-herbal formulations to cure various ailments like arthritis, wound and injury, dysentery, fever, snake bite, jaundice, diabetes, hypertension , asthma, stone remover, eye infection, menstrual disorder, burn, allergy, toothache, fever, headache, pneumonia etc.Conclusion: All together 31 species of plants of 25 families were found to be used as traditional medicines formulation during the study. 24 different types of formulations have been observed throughout the research. Five different types of dosage forms were used. Nelumbo nucifera was widely used for the treatment of Jaundice than other allopathic medicine.